Ultrastructural study for the gonadotrophs and somatotrophs of the pituitary gland in aging rabbits of local bread (oryctolagus cuniculus) - Idrees khalaf Thamer (Tikrit Journal of Pure Science, 2023)
Eighteen rabbit of local bread were classified into3 groups A, B, and C